(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Crotalaria ramosissima Roxb. (Fabales: Fabaceae) is a common weed that grows prolifically in few areas of Karnataka. The plant used as insect repellent in grain storage room and C. ramosissima leaves used to treat skin diseases. The purpose of study was to investigate phytochemical constituents and evaluate their antibacterial and antioxidant properties along with bioactive compound profiling. Phytochemical screening of ethyl acetate, ethanol and methanol extracts revealed presence of necessary phytochemical components, anti-microbial activity against plant pathogens showed best results from ethyl acetate extract with MIC 15.60µg mL-1 against Pseudomonas syringae and Xanthomonas oryzae with MIC 31.25µg mL-1, confirmed with TLC bio-autography, DPPH antioxidant assay, showed the highest activity of IC-50 2.71µg mL-1 from methanol extract with standard reference, Gas chromatography/Mass spectroscopy (GC-MS) used for profiling to detect chemical compounds from plant solvent extracts which showed presence of 21 compounds, ethyl acetate extract identified with 1,2,4-Oxidiazole, 3-(1,3-bezodioxol-5-y-5-[2-(4-methoxyphenyl)-ethyl] which is heterocyclic aromatic compound of azole family-alkaloid, which is reported for the first time in C. ramosissima. The results revealed significant properties and the obtained 1,2,4-oxidiazole derivative can be a novel bio-control agent against microorganisms and for crop protection. It also retained current researcher's attention from its biological properties in pharmaceutical drug industry.